Overhandiging van de S.M.K. legpenning aan Oosterbeek (rechts). Zie voor de penning BG H14/16 en voor de oorkonde C18/45
Overhandiging van de S.M.K. legpenning aan Oosterbeek (rechts). Zie voor de penning BG H14/16 en voor de oorkonde C18/45.